SIMPLE DESALINATION PROCESS FOR MAKING AGRICULTURAL CULTIVATION SOLUTION FROM SEAWATER USING NATURAL ZEOLITE AND ACTIVATED ALUMINA - Wajima, Takaaki (MATTER: International Journal of Science and Technology, 2019)
We attempted to make agricultural cultivation solution from seawater with a two-step process using natural zeolite and activated alumina. Natural zeolite used in this study is Japanese mordenite-type zeolite with high content of Ca2+ as exchangeable cation. Activated alumina can remove anions, SO42- and Cl-, and divalent cations, Mg2+ and Ca2+, better than monovalent cations, Na+ and K+, from seawater. By treating seawater with natural zeolite, the obtained solution contains higher divalent cations and lower monovalent cations than seawater, due to the ion exchange of natural zeolite, and removal of cations from the obtained solution is higher than that from seawater using activated alumina, while removal of anions is almost same. Radish sprouts can be grown in the solution after two-step treatment of natural zeolite and activated alumina, while they cannot be grown in seawater and the solutions after one-step treatment of natural zeolite and activated alumina.